A Joint Biological and Microbiological Analysis of Immune and Cellular Responses to Pathogenic Microorganism - Shukur, Wameedh Sabah; Hami, Noor Al-Huda Lafteh Baid; Jassim, Safa Safaa Muneer (American Journal of Biology and Natural Sciences, 2025)
Research on immunity and host-pathogen interactions spans an immense range of topics but can often be divided into biological and microbiological perspectives. Biological approaches centre on cellular and humoral responses, delineating factors such as signalling and immunometabolism that shape both effector responses and pathogen control. By contrast, microbiological approaches focus on the diversity of pathogens, their interaction with a given host, and the resulting host responses. Biologists have called for the micrometric complexity of pathogens and host-pathogen interactions to be integrated with the macroscopic physiology and cellular interactions considered in immunology. More broadly, compelling case studies illustrate the power and usefulness of joining biological and microbiological analyses. Contemporary biologists emphasise the universality of the immune system and its extraordinary capacity to adapt, while microbiologists highlight the immense variety of infecting pathogens and the consequent diversity of host responses. Just as biological concepts such as memory, amplification, and education are fundamental to microbiology, the extraordinary diversity of infecting agents and associated host responses has much to offer contemporary biology. Vaccination has been termed one of the great triumphs of science and is juxtaposed with cancer, antibiotic resistance, and emerging pathogens among the grand challenges for humankind.